Optical Evaluation of In Situ Crack Propagation by Using Mechanoluminescence of SrAl2O4:Eu2+, Dy3+. Issue 7 (28th March 2015) - Timilsina, Suman; Lee, Kwang Ho; Kwon, Yong Nam; Kim, Ji Sik; Reimanis, I.
<x xml:space="preserve">Abstract</x> New theoretical solutions involving conventional crack propagation from static to dynamic fracture in terms of mechanoluminescence (ML) and the experimental techniques to trace the in situ crack and its instantaneous stress intensity factor (SIF) have been suggested in SrAl2O4:Eu2+, Dy3+ (SAO). The direct optical method to determine the moving crack tip on behalf of ML was verified by indirect crack mouth opening displacement (CMOD). The mode I SIF <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1n9xfw9p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />KIML</alternatives> calculated from the instantaneous cumulative ML fringes showed proper agreement with the SIFs <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1n9xfw7k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />KIaML</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1n9xfw4x" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />KIa(CMOD)</alternatives> acquired from conventional ASTM E‐399 measurements under quasidynamic condition. The magnitude and shape of the theoretically predicted crack tip stress field was in accordance with the experimental in situ ML evidence while determining the quasidynamic SIF from the cumulative ML intensity. Therefore, the use of ML technology could be one of the possible substitutive and substantial alternatives for structural health monitoring systems due to its simplicity but effectiveness in detecting arrested or propagating crack tips and in assessing the instantaneous structural integrity by means of the ML fracture parameters.